2017
DOI: 10.1016/j.molcel.2017.04.012
|View full text |Cite|
|
Sign up to set email alerts
|

Structure and Dynamics of a 197 bp Nucleosome in Complex with Linker Histone H1

Abstract: SUMMARY Linker histones associate with nucleosomes to promote the formation of higher-order chromatin structure, but the underlying molecular details are unclear. We investigated the structure of a 197 base-pair nucleosome bearing symmetric 25 base-pair linker DNA arms in complex with vertebrate linker histone H1. We determined electron cryo-microscopy (cryo-EM) and crystal structures of unbound and H1-bound nucleosomes and validated these structures by site-directed protein cross-linking and hydroxyl radical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

23
202
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(248 citation statements)
references
References 69 publications
23
202
0
Order By: Relevance
“…In addition, the tails of H1.4 were largely not observable in this cryo-EM study 47 , suggesting that they do not stably bind to linker DNA in any specific manner. Intriguingly, the globular domain of human H1.5, which has essentially the same amino acid sequence as the globular domain of H1.4 (BOX 2), was found to bind the dyad in single nucleosomes 38,44 . It has been suggested that the difference in the binding mode between the single chromatosome and the nucleosome array could be caused either by glutaraldehyde crosslinking used in the cryo-EM experiment or by the folded structure of the nucleosome array, in which re-orientation of the linker DNA disrupts the intrinsic on-dyad binding mode 44 .…”
Section: Roles In Chromatin Organizationmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, the tails of H1.4 were largely not observable in this cryo-EM study 47 , suggesting that they do not stably bind to linker DNA in any specific manner. Intriguingly, the globular domain of human H1.5, which has essentially the same amino acid sequence as the globular domain of H1.4 (BOX 2), was found to bind the dyad in single nucleosomes 38,44 . It has been suggested that the difference in the binding mode between the single chromatosome and the nucleosome array could be caused either by glutaraldehyde crosslinking used in the cryo-EM experiment or by the folded structure of the nucleosome array, in which re-orientation of the linker DNA disrupts the intrinsic on-dyad binding mode 44 .…”
Section: Roles In Chromatin Organizationmentioning
confidence: 98%
“…This crystal structure is in agreement with previous in vitro experimental data investigating the binding of the H5 globular domain to nucleosomes 41,42 , as well as data showing the binding of the globular domain of mouse H1.0 and its mutants to chromatin in vivo 36 , suggesting that the linker histone binds to the nucleosome in the same way in vitro and in vivo . Using longer linker DNA and full-length linker histone H1.0, it was further shown by NMR and cryo-electron microscopy (cryo-EM) that the tails of the linker histones and the longer linker DNA in the chromatosome do not have a role in determining the binding mode between the nucleosome and the globular domain of the linker histone 43,44 . However, measurements of binding affinity and cryo-EM structural studies showed that within a single chromatosome, the C-terminal tail of H1.0 appears to be preferentially associated with only one of the two available linker DNAs 44,45 , which was speculated to have a role in influencing the assembly and properties of higher-order chromatin structures 44 .…”
Section: Roles In Chromatin Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The most abundant chromatin-binding protein in the majority of eukaryotes is the linker histone H1, which binds at the dyad axis of the nucleosome and plays roles in genomic access, gene regulation, and compaction in cells 23 . Given recent reports that the lysine-rich C-terminal tail of histone H1 can form coacervates with DNA 24 , we wondered how binding of histone H1 to nucleosomal arrays ( Fig.…”
mentioning
confidence: 99%
“…X-ray crystallography [4,44,45] and cryo-EM [43,[46][47][48][49] measurements of the nucleosome show that histonebound DNA is well approximated by a deformed B-DNA structure, wrapping the histone octamer 1.7 times in a superhelix with a radius of 4.19 nm and a pitch of 2.59 nm [45]. Thus, Ω entry and Ω exit are well defined as a function of the number of bound nucleotides to the histone core.…”
mentioning
confidence: 99%